The Fusion Drummer: 52 beats for the Jazz-Rock Player - HOULLIB, Murray (Alfred Publishing Co., Inc, 1980)
contains hip betas in the style of: Steve Gadd, Billy Cobham, Harvey Mason, Lenny White, Airto Moreira, Terry Bozzio, Ndugu, and Chris Parker